Navigating Researcher Developer career trajectories: a perspective from beyond Higher Education - John Miles (Journal of Learning Development in Higher Education)
This opinion piece explores the evolving professional landscape for Researcher Developers within and beyond the confines of academia, reflecting on the author's experiences as a former researcher and Researcher Developer. It discusses the multifaceted skill set required in the Researcher Developer role and considers the opportunities for Researcher Developers to advance within their institutions or pivot to roles in different sectors, exploiting their unique skills and experience. The importance of collaboration is underscored as an essential element for professional advancement, and synergies are drawn between the mindset of Researcher Developers and that of entrepreneurs, advocating for recognition of their critical contribution to the academic ecosystem and beyond.